Analyzing Pronouns In Analytical Exposition Text - Sitanggang Anita; Delfia Sitompul; Nikita Gabriela Sitanggang; Eka Risti Pasaribu (Jurnal Penelitian Multidisiplin, 2023)
In learning English, we start from learning the basic things. The basic things are parts of speech. Parts of speech consist of noun, pronoun, verb, adjective, adverb, preposition, conjunction, and interjection. The frequently used of pronoun in our everyday life is one of inspirations of this research. By knowing pronouns, a person can make simple sentences that can be used to master vocabulary and to motivate someone to be fluent in English. The aim of this research is to find out the percentage of subject pronouns in analytical exposition text. The method which is applied in this analytical exposition text is a descriptive qualitative. The result of this research shows that subject pronoun “I”;”We”; “You” and “It” in analytical exposition text is dominant that is 35.2% than other pronouns.